The Influence of SMAW Welding Current Variation on Tensile Strength, Corrosion Rate, and Microstructure of ST 42 Steel for Inner Bottom Plate Material in Ships - Parlindungan Manik; Deddy Chrismianto; Putranda Firman Prayoga (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Steel is currently widely used in the industrial world. Due to its versatile uses, the development of steel science has also broadened, leading to improved steel processing methods. Welding is a process of joining two pieces of metal using heat. Steel, containing carbon, is prone to oxidation and rust. The aim of this study is to determine the influence of welding current variations on tensile strength, corrosion rate, and the micrographic structure of ST 42 steel. The research method employed is experimental. The welding current variations used are 70 A, 85 A, 100 A, 115 A, and 130 A. In this study, the highest average tensile stress was found at 130 A, measuring 519.20 MPa. For tensile strain, the highest values of 7% were observed at 115 A and 130 A. The highest modulus of elasticity was obtained at 115 A, with a value of 102.18 GPa. The highest corrosion rate occurred in specimens with 70 A, with a value of 0.19 mm/year (good), and the lowest corrosion rate was at 130 A, with a value of 0.10 mm/year (excellent). The micrographic structure testing results showed a decrease in the ferrite phase with each increase in current, while the pearlite phase increased. It can be concluded that the best welding current for ST 42 steel is at 130 A, due to its high tensile strength and low corrosion rate.